2021
DOI: 10.1111/iej.13459
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric and immunohistochemical study shows that tricalcium silicate cement associated with zirconium oxide or niobium oxide is a promising material in the periodontal tissue repair of rat molars with perforated pulp chamber floors

Abstract: Barbosa DD, Delfino MM, Guerreiro-Tanomaru JM, Tanomaru-Filho M, Sasso-Cerri E, Silva GF, Cerri PS. Histomorphometric and immunohistochemical study shows that tricalcium silicate cement associated with zirconium oxide or niobium oxide is a promising material in the periodontal tissue repair of rat molars with perforated pulp chamber floors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…In addition, the pure TCS provided a greater deposition of hydroxyapatite after immersion in physiological solution than the PC (Camilleri, 2011). Thus, experimental TCS materials have been proposed as alternative materials to the WMTA‐Angelus (Barbosa et al, 2021; Camilleri et al, 2013; Camilleri, Grech, et al, 2014; Grech et al, 2013; Queiroz, Torres, Rodrigues, Viola, Bosso‐Martelo, Chavez‐Andrade, Guerreiro‐Tanomaru, & Tanomaru‐Filho, 2021; Queiroz, Torres, Rodrigues, Viola, Bosso‐Martelo, Chavez‐Andrade, Souza, et al, 2021; Taha et al, 2021). Several agents, such as niobium oxide, zirconium oxide and calcium tungstate, have provided adequate radiopacity to the calcium silicate‐based materials for use as endodontic repair filling material (Barbosa et al, 2021; Bosso‐Martelo et al, 2016; Queiroz, Torres, Rodrigues, Viola, Bosso‐Martelo, Chavez‐Andrade, Guerreiro‐Tanomaru, & Tanomaru‐Filho, 2021; Silva et al, 2014, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the pure TCS provided a greater deposition of hydroxyapatite after immersion in physiological solution than the PC (Camilleri, 2011). Thus, experimental TCS materials have been proposed as alternative materials to the WMTA‐Angelus (Barbosa et al, 2021; Camilleri et al, 2013; Camilleri, Grech, et al, 2014; Grech et al, 2013; Queiroz, Torres, Rodrigues, Viola, Bosso‐Martelo, Chavez‐Andrade, Guerreiro‐Tanomaru, & Tanomaru‐Filho, 2021; Queiroz, Torres, Rodrigues, Viola, Bosso‐Martelo, Chavez‐Andrade, Souza, et al, 2021; Taha et al, 2021). Several agents, such as niobium oxide, zirconium oxide and calcium tungstate, have provided adequate radiopacity to the calcium silicate‐based materials for use as endodontic repair filling material (Barbosa et al, 2021; Bosso‐Martelo et al, 2016; Queiroz, Torres, Rodrigues, Viola, Bosso‐Martelo, Chavez‐Andrade, Guerreiro‐Tanomaru, & Tanomaru‐Filho, 2021; Silva et al, 2014, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At 7, 15, and 30 days, the number of IL‐6‐immunolabeled cells was significantly greater around Bio‐C Pulpo and Biodentine specimens than in WMTA specimens. However, it is important to emphasize that IL‐6 is a pro‐inflammatory cytokine detected in endothelial cells, fibroblasts and inflammatory cells 27,38,53 . In the present study, immunoexpression of IL‐6 was computed in different cell types (inflammatory cells, endothelial cells and fibroblasts).…”
Section: Discussionmentioning
confidence: 87%
“…54,55 Several studies have demonstrated that IL-6 is responsible for the maintenance of inflammatory reaction and, the reduction of this cytokine is associated with tissue connective remodeling, allowing the formation of extracellular matrix components and fibroblasts proliferation. 27,36,38,53,56 In fact, no significant difference in the number of IL-6-immunostained cells and inflammatory cells was observed among the groups, including in the CG specimens, at 60 days, indicating that bioceramic materials are biocompatible.…”
Section: Birefringent Collagen In the Capsulesmentioning
confidence: 84%
See 2 more Smart Citations